A Cytogenetic Analysis to Document the Prevalence Autosomal Trisomy in Eastern Uttar Pradesh Region: An Observational Study - Priyanka Pandey; Rakesh Kumar Verma; Navneet Kumar; Sciddhartha Koonwar (Advanced Research in Biological Science Vol. 4, 2023)
The study carried out a postnatal cytogenetic evaluation of suspected cases of autosomal trisomies in both genders to report their frequency, types and their various cytogenetic variants in Eastern Uttar Pradesh and also correlate them with maternal age. Trisomies are syndromes resulting from the presence of an additional copy of all or a part of an autosomal chromosome (three copies instead of the usual two). This can occur via meiotic nondisjunction (producing a gamete with two copies of a chromosome instead of one) or a Robertsonian translocation (where the chromosomal material is rearranged but balanced in a parent and becomes unbalanced after chromosomal separation). It often happens as a result of chromosomal non-disjunction during meiosis. The most often seen autosomal trisomies are trisomy 21, also known as Down syndrome, trisomy 18, sometimes known as Edward syndrome, and trisomy 13, also known as Patau syndrome. Trisomy 8, Trisomy 9, and Trisomy 2 are other uncommon trisomies. Cytogenetic methods that aid in the detection of various chromosomal abnormalities connected to these trisomy syndromes are used to confirm trisomy syndromes. Karyograms of suspected cases of trisomies was prepared from the peripheral blood using GTG banding technique Using the standard protocols. The karyograms were analysed using cytovision software. Out of 52 suspected cases of trisomy; karyograms could be obtained in 46 cases. Out of these 46 cases 43 (93.5%) had trisomy 21 and 6 cases showed no abnormality. Other trisomy disorders could not be reported. Among patients with Down syndrome, free trisomy (n=40; 93%) was reported to be the most common variant followed by Robertsonian translocation (n=2; 4.7%) and mosaic trisomy (n=1; 2.3%) respectively. It was more common in males (n=27; 62.7%) than females (n=16 ;37.3%) Male to female ratio of Down syndrome patients was 1.68. 50% of patients with Down syndrome were born to mothers falling in age group of 36-40 y. Down"s syndrome was found to be the most common trisomy disorder in Lucknow region. Hence it is important to carry out a cytogenetic analysis of all the suspected cases to confirm the diagnosis, so that they can be managed appropriately for various clinical co-morbidities.